Social determinants of health-based strategies to address vaccination disparities through a university-public health partnership - Susie Crowe; Carlyn Kimiecik; Omolola A. Adeoye-Olatunde; Megan Conklin; Jordan Smith; Sonak D. Pastakia; Alicia Dinkeldein; Mary Dubinin; Peter Zubler; Jasmine D. Gonzalvo (Journal of Clinical and Translational Science, 2024)
A decline in routine vaccinations, attributed to vaccine hesitancy, undermines preventative healthcare, impacting health and exacerbating vaccine disparities. University-public health partnerships can improve vaccination services. This study describes and evaluates a university-public health use case employing social determinants of health (SDoH)-based strategies to address vaccination disparities. Guided by the Translational Science Benefits Logic Model, the partnership offered no-cost preventative vaccines at community-based organization (CBO) sites, collected CBO clientele’s vaccination interest, hesitancy, and demographic data, and conducted descriptive analyses. One hundred seven vaccination events were held, administering 3,021 vaccines. This partnership enhanced health outcomes by addressing disparities through co-located vaccination and SDoH services.